Pemanfaatan Zeolit Alam Ende Sebagai Katalis Pada Pirolisis Polietilena Dari Sampah Plastik - Gregorio Antonny Bani (Jurnal Ilmiah Teknik Kimia, 2023)
This study aims to characterizing zeolite Ende became a catalyst in the pyrolysis of polyethylene plastic waste; determine the influence of zeolite catalyst to the activation energy of the pyrolysis; determine the influence of temperature in the pyrolysis; determine the influence of a catalyst in the pyrolysis; determine the influence of the interaction between temperature and the catalyst. Based on the experimental results, it is known that the activation process can alter the chemical properties and physical properties of natural zeolite Ende include crystallinity, surface area, pore volume and pore, as well as its acidity to serve as a catalyst; zeolite catalyst on the pyrolysis process of polyethylene plastic waste can lower the activation energy of up to 4371.1 cal/mol; 0.10 is the best composition of the use of natural zeolite active Ende as a catalyst in the pyrolysis process of polyethylene plastic waste; the best interaction between temperature and active natural zeolite catalysts Ende is on the treatment temperature of 400 ° C and 0.10 catalyst composition.